Oral health related quality of life of children and adolescents affected by rare orofacial diseases: a questionnaire-based cohort study - Lisa Friedlander; Ariane Berdal; Priscilla Boizeau; Brigitte Alliot Licht; Marie-Cécile Manière; Arnaud Picard; Olivier Azzis; Marie-Paule Vazquez; Corinne Alberti; Muriel De La Dure Molla (Orphanet Journal of Rare Diseases, 2019)
Abstract Background Rare diseases affecting the teeth, the oral cavity and the face are numerous, each of them present specific characteristics, and is a life-long condition. The aim of the study was to assess the association between Oral health-related quality of life (OHRQoL), and demographic characteristics, clinical and dental factors, and psycho-social characteristics to investigate that oral symptoms are not the main factors underlying a decrease in OHRQoL. Material and methods We conducted a national cohort study in French centres for rare diseases (RD) specialized in orofacial diseases. The inclusion criteria were: to have received care in RD centres over the last 5 years (2012–2017) and to have been between 6 and 17 years of age on September 1, 2017. Patients were invited to answer a questionnaire composed of socio-demographic, clinical and dental questions, psychosocial questions and then fill in the Child-OIDP Index. At the end of the questionnaire, a free space was left for the patient to add a verbatim comment to provide qualitative data. Thematic analysis was used to analyze the verbatim answers. Results Complete data were available for 110 patients. The sample included 44.5% boys and 55.5% girls. Ages ranged from 6 to 17 years old and 68.2% were between 6 to 12 years old and 31.8% were between 13 and 17 years old. Factor associated with a lower OHRQoL were: being a girl (p = 0.03), renouncement to dental care for financial reasons (p = 0.01), having syndromic disease (p = 0.01), having a problem with tooth shape and color (p = 0.03), feeling isolated, alone and different from other children (p = 0.003 and p = 0.02). Qualitative analysis highlighted very little recourse to psychological care and patients reported great anxiety and fear about the future. Conclusion OHRQoL of children suffering from these diseases is impaired, especially from the psychosocial point of view but also from that of the course of treatment and access to care. There is a need to improve the legibility of care pathways and the financial coverage of treatments.